2017
DOI: 10.1016/j.bbamem.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the killing activity of an antimicrobial peptide active against extensively antibiotic-resistant K. pneumon iae and P. aeruginosa

Abstract: SET-M33 is a multimeric antimicrobial peptide active against Gram-negative bacteria in vitro and in vivo. Insights into its killing mechanism could elucidate correlations with selectivity. SET-M33 showed concentration-dependent bactericidal activity against colistin-susceptible and resistant isolates of P. aeruginosa and K. pneumoniae. Scanning and transmission microscopy studies showed that SET-M33 generated cell blisters, blebs, membrane stacks and deep craters in K. pneumoniae and P. aeruginosa cells. NMR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
4
18
0
Order By: Relevance
“…In contrast, it showed better MBC value, produced high bacteriocidal activity, which can be compared with our previous article [ 22 ]. Time-kill kinetics findings showed a rapid decline and regrowth of Escherichia coli cells after 12 h, which is consistent with the kinetics of other antimicrobial peptide reports [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, it showed better MBC value, produced high bacteriocidal activity, which can be compared with our previous article [ 22 ]. Time-kill kinetics findings showed a rapid decline and regrowth of Escherichia coli cells after 12 h, which is consistent with the kinetics of other antimicrobial peptide reports [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…The capsule of K. pneumoniae is known to inhibit host antimicrobial peptide activity and complement lysis by acting as a penetration barrier (8). Although the capsule inhibits the activity of host antimicrobial peptides, there have been synthetic peptides identified with potent activity toward this species (50)(51)(52). However, no studies have aimed to determine how K. pneumoniae active peptides are superior to host antimicrobial peptides in their ability to penetrate the bacterial capsule.…”
Section: Discussionmentioning
confidence: 99%
“…SET-M33 is a branched peptide, composed of 40 amino acids, grouped in branches of 9-mers on a three-lysine scaffold. Its mechanism of action is based on multistep interference with bacterial membranes [17]. First it is attracted to the bacterial surface by the anionic LPS coating.…”
Section: Discussionmentioning
confidence: 99%
“…First it is attracted to the bacterial surface by the anionic LPS coating. Close to the lipid double layer it takes on amphipathic helix structure and becomes partially embedded in the bacterial plasma membrane, causing loss of membrane function [17]. Previous CD studies on SET-M33 and on a monomeric analogue, showed that helix formation is only observed in the presence of micelle-like structures [17].…”
Section: Discussionmentioning
confidence: 99%